Enantioselective separation using chiral amino acid functionalized polyfluorene coated on mesoporous anodic aluminum oxide membranes - Nikam, Shrikant B.; Asha, S. K. (Analytical Chemistry, 2020)
Homochiral mesoporous anodic aluminum oxide membranes (AAO) were prepared by coating protected chiral D/L aspartic acid appended polyfluorene in the pores. These chiral AAO membranes successfully demonstrated enantioselective recognition and separation of a range of amino acids from their aqueous racemic mixture by simple filtration. Enantioselective separation was achieved by selective adsorption of one enantiomer from the aqueous racemic mixture into the chiral pores of the AAO membrane leaving the filtrate enriched with the other enantiomer. Extraction and quantification of the adsorbed amino acid (glutamic acid) demonstrated that 1 mg of homochiral polyfluorene could effectively extract about 3.5 mg of glutamic acid with 95% enantiomeric excess in 24 h. This is one of the highest enantiomeric excesses (ee %) and yields reported so far in the literature for a racemic mixture of glutamic acid. The pore size of the AAO membrane influenced the efficiency of separation with a reduction in pore size from 200 to 20 nm leading to reduced ee % (similar to 95% to similar to 28%). These results raise the possibility for a facile method to carry out enantioselective separation.

Five concomitant polymorphs of a green fluorescent protein chromophore (GFPc) analogue: understanding variations in photoluminescence with pi-stacking interactions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Nikam, Shrikant B.; Puthuvakkal, Anisha; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Acta Crystallographica Section B-Structural Science Crystal Engineering and Materials, 2020)
The synthetically modified green fluorescent protein chromophore analogue 3,4,5-trimethoxybenzylidene imidazolinone (1) yielded five polymorphs (I, II, III, IV, V) concomitantly irrespective of the solvent used for crystallization. The pentamorphic modification of 1 is solely due to the interplay of iso-energetic weak intermolecular interactions in molecular associations as well as the conformational flexibility offered by a C-C single bond, which connects the electron-deficient moiety imidazolinone with the electron-rich trimethoxybenzylidene group. A common structural feature observed in all the polymorphs is the formation of a `zero-dimensional' centrosymmetric dimeric unit through a short and linear C-H center dot center dot center dot O hydrogen bond engaging phenyl C-H and imidazolinone carbonyl oxygen. However, the networking of these dimeric units showed a subtle difference in all the polymorphs. The 2D isostructurality was observed between polymorphs I, II and III, while the other two polymorphs IV and V revealed only `zero-dimensional' isostructurality. The different fluorescence emissions of Form I (blue) and Forms II to V (yellow) were attributed to the differences in pi-stacking interactions. It shows that one can modulate the photophysical properties of these smart materials by slightly altering their crystal structure. Such an approach will aid in developing new multi-colour organic fluorescent materials of varying crystal structures for live-cell imaging and fluorescent sensing applications.
Keywords: green fluorescent protein; hydrogen bonds; isostructurality; photoluminescence; pi-stacking; Polymorphs

Enantioselective separation using chiral amino acid functionalized polyfluorene coated on mesoporous anodic aluminum oxide membranes (vol 92, pg 6850, 2020) - Nikam, Shrikant B.; Asha, S. K. (Analytical Chemistry, 2021)

Enantioselective separation of amino acids using chiral polystyrene microspheres synthesized by a post-polymer modification approach - Nikam, Shrikant B.; Asha S. K (ACS Polymers Au, 2022)
The enantioselective separation of a racemic mixture of amino acids was achieved by chiral amino acid-modified polystyrene (PS) that was developed by a post-polymer modification approach. Styrene was polymerized using the reversible addition–fragmentation chain-transfer (RAFT) polymerization technique and further post-polymer modification was applied by Friedel–Crafts acylation reaction with chiral N-phthaloyl-<span class="smallcaps smallerCapital" style="box-sizing: border-box; outline: none; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-caps: small-caps; font-variant-alternates: normal; color: rgb(0, 0, 0); font-family: georgia, serif; font-size: 17.008px; background-color: rgb(244, 244, 244);">l-leucine acid chloride to obtain the protected PS-<span class="smallcaps smallerCapital" style="box-sizing: border-box; outline: none; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-caps: small-caps; font-variant-alternates: normal; color: rgb(0, 0, 0); font-family: georgia, serif; font-size: 17.008px; background-color: rgb(244, 244, 244);">l-Leu. The chiral PS (protected PS-<span class="smallcaps smallerCapital" style="box-sizing: border-box; outline: none; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-caps: small-caps; font-variant-alternates: normal; color: rgb(0, 0, 0); font-family: georgia, serif; font-size: 17.008px; background-color: rgb(244, 244, 244);">l-Leu) was assembled into microspheres using a surfactant and was used for carrying out the enantioselective separation of amino acid racemic mixtures by enantioselective adsorption followed by a simple filtration process. Compared to as-precipitated chiral PS (protected PS-<span class="smallcaps smallerCapital" style="box-sizing: border-box; outline: none; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-caps: small-caps; font-variant-alternates: normal; color: rgb(0, 0, 0); font-family: georgia, serif; font-size: 17.008px; background-color: rgb(244, 244, 244);">l-Leu) powder, the protected PS-<span class="smallcaps smallerCapital" style="box-sizing: border-box; outline: none; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-caps: small-caps; font-variant-alternates: normal; color: rgb(0, 0, 0); font-family: georgia, serif; font-size: 17.008px; background-color: rgb(244, 244, 244);">l-Leu microspheres exhibited a better enantioselective separation efficiency (ee %). Furthermore, the protected PS-<span class="smallcaps smallerCapital" style="box-sizing: border-box; outline: none; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-caps: small-caps; font-variant-alternates: normal; color: rgb(0, 0, 0); font-family: georgia, serif; font-size: 17.008px; background-color: rgb(244, 244, 244);">l-Leu was deprotected to obtain the amine-functionalized deprotected PS-<span class="smallcaps smallerCapital" style="box-sizing: border-box; outline: none; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-caps: small-caps; font-variant-alternates: normal; color: rgb(0, 0, 0); font-family: georgia, serif; font-size: 17.008px; background-color: rgb(244, 244, 244);">l-Leu chiral PS, which was also assembled into microspheres and used for carrying out enantioselective separation. Deprotected PS-<span class="smallcaps smallerCapital" style="box-sizing: border-box; outline: none; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-caps: small-caps; font-variant-alternates: normal; color: rgb(0, 0, 0); font-family: georgia, serif; font-size: 17.008px; background-color: rgb(244, 244, 244);">l-Leu-functionalized chiral PS microspheres could achieve up to 81.6 ee % for the enantioselective separation of a racemic mixture of leucine. This is one of the first reports of the synthesis of amino acid-modified chiral PS microspheres and their application to the simple filtration-based enantioselective separation of native amino acids from their racemic mixtures.

Structure-property insights into chiral thiophene copolymers by direct heteroarylation polymerization - Nikam, Shrikant B.; Singh, Chandrodai Pratap; Krishnamurty, Sailaja; Asha, S. K. (European Polymer Journal, 2022)
Chiral thiophene copolymers with fluorene as co monomer are designed having N-Boc-L-glutamic acid-1-tert-butyl ester as a chiral substituent located either on the thiophene unit or the fluorene unit with varying spacer length. The atom-economic direct heteroarylation polymerization (DHAP) method is utilized for the polymerization. Gibb's free energy (delta G) for polymerization determined using DFT calculations indicate difficulty in achieving high molar mass when the bulky chiral substituents are attached through short spacer to the backbone. The experimental observations are in agreement with the theoretical calculations with no polymer-ization or very low molar mass sticky compounds obtained for reactions with predicted + & UDelta;G values. Structure -property relationship are compared for two chiral polymers -P4 and P5 having the chiral substitution on thiophene and fluorene units respectively. No CD signal is observed in THF-a good solvent where the polymers are molecularly dissolved. Intense bisignated CD signal is observed for both polymers upon addition of methanol - a poor solvent, to their THF solution. The bisignate CD signal with maxima at lower wavelength and inflection point associated with the pi-pi* absorption band is characteristic of exciton coupling between polymer chains in a left handed helical orientation. Small differences are observed in the intensity of the CD signal for the polymers P4 and P5 highlighting the impact of steric hindrance of bulky pendant groups on polymer conformation. DHAP is an atom economic polymerization procedure that can be gainfully utilized for developing chiral conjugated polymers.
Keywords: chiral; DFT; Direct heteroarylation polymerization; Gibb?s free energy; Steric Hindrance